Level of development of e-commerce in EU countries = Poziom rozwoju e-commerce w krajach UE - Jędrzejczak-Gas, Janina; Barska, Anetta; Siničakova, Marianna (Zielona Góra: Faculty of Economics and Management Press)
E-commerce in Europe is becoming increasingly important in all market segments, and in most segments it already accounts for few or even several dozen percent of total trade. According to a report by E-commerce Europe, it has already left the US market behind in 2010. Year by year, the willingness to buy products, which until recently were not treated by many consumers as "online", such as food products, is growing.
Keywords: e-commerce; rozwój; państwa EU-28; metoda Hellwiga; handel internetowy; development; EU-28 countries; Hellwig method